2009
DOI: 10.1002/ejoc.200900147
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Optical Properties of Regioisomerically Pure Alkynyl‐Bridged Bis(phthalocyanines)

Abstract: PbII ethynyl-and butadiynyl-bridged bis(phthalocyaninates) 1a-d, peripherally functionalized with n-butoxy moieties, have been synthesized by using Pd-catalyzed cross-coupling methodologies. Preliminary open-aperture Z-scan experiments with nanosecond pulses at 550 nm on solutions of Pb II

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 82 publications
0
10
0
Order By: Relevance
“…Several single-crystal X-ray structures have been reported. 63,92,176,185,194,203,204,207,[209][210][211]237,240,260,262,321,330,334,335,[337][338][339]360,392,402 Work by Barrett and Hoffman 203,204,207,[209][210][211]334,335,[337][338][339]392 on Pz compounds has been particularly prominent in this regard, in recent years. There has been a growing focus on excited state properties over the past decade.…”
Section: Other Characterization Methodsmentioning
confidence: 99%
“…Several single-crystal X-ray structures have been reported. 63,92,176,185,194,203,204,207,[209][210][211]237,240,260,262,321,330,334,335,[337][338][339]360,392,402 Work by Barrett and Hoffman 203,204,207,[209][210][211]334,335,[337][338][339]392 on Pz compounds has been particularly prominent in this regard, in recent years. There has been a growing focus on excited state properties over the past decade.…”
Section: Other Characterization Methodsmentioning
confidence: 99%
“…The OL effect at 532 nm generated by the peripherally bridged dimeric species ( t -Bu) 3 PcMX­( t -Bu) 3 PcM with X = alkynyl (−CC−), and M = Co, Zn ( 687a – c , Chart ), has been also studied. , The species 687a displayed the highest merit factor among the various peripherally alkynyl bridged Pc dimers σ exc /σ 0 = 11. Moreover, the comparison between the OL performance of 687a and its starting monomer demonstrated that the dimerization leads to molecular systems with a larger merit factor.…”
Section: Phthalocyanines and Related Macrocyclesmentioning
confidence: 99%
“…On the same line, Pb II Pc dimers 67 were synthesized in the search for materials with enhanced optical‐limiting characteristics that exhibited a decrease in transmittance upon an increase in the incident light intensity 65. Considering that heavy‐metal atoms in the central cavity of a Pc usually contribute to an increase in the population of the triplet state via intersystem crossing, leading to improved OL properties, the synthesis of Pb II Pcs was targeted.…”
Section: Synthetic Examples Of Advanced Pc‐based Architecturesmentioning
confidence: 99%